PENGEMBANGAN EXCITED MATH GAMES UNTUK MENINGKATKAN PEMAHAMAN KONSEP HIMPUNAN SISWA SMP - Ramadhani, Zahrotul Luthfina; Cipta, Dyah Ayu Sulistyaning; Kartika, Era Dewi (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2023)
The aim of the research is to develop interactive learning media Excited Math Games on set material for class VII junior high school students. The research method used is development research referring to the ADDIE model. The research instruments were media development sheets and student learning outcomes tests. The results of the research are based on the design carried out (1) analysis: needs analysis which shows that the use of learning media is still limited, and students have not been actively involved in the learning process, technology analysis, a combination of Power Point and iSping Suite 10 used as the main software, and curriculum analysis according to with the 2013 curriculum; (2) design: collecting references, designing material content according to aspects of understanding concepts, preparing stoyboards and flowcharts to make it easier to create learning media; (3) development; creating learning media, expert validation to determine the validity of learning media, and revising phase I products based on validator input; (4) implementation: trial to obtain data on students' level of understanding of concepts after applying learning media; (5) evaluation: analyzing student learning test results to determine the level of understanding of concepts. The quality of the learning media developed meets the very valid criteria based on the assessment of media experts and material experts with scores of 3.8125 and 3.65 respectively. Meanwhile, the level of understanding of students' concepts after applying the Excited Math Games learning media obtained very high criteria based on student learning outcomes tests with a completeness percentage of 86.67% and an average score of 88 or above the students' completeness score, namely > 70.